The Influence of Brand Image, Social Media Advertisement, and Word of Mouth Toward Customer Attraction at Alvina Hotel, Pematang Siantar - Natalia Haudy (International Journal of Economics, Business Management and Accounting (IJEBMA), 2019)
This study investigates the collective impact of brand image, social media advertisement, and word of mouth on customer attraction at Alvina Hotel in Pematang Siantar. Through a mixed-methods approach encompassing surveys and qualitative interviews, the research illuminates the intricate relationships between these factors. Results highlight the pivotal role of a positive brand image in fostering customer interest and the potential of strategic social media campaigns to expand the hotel's reach. Additionally, the study underscores the enduring influence of word of mouth in shaping potential guests' perceptions and decisions. By delving into these dynamics, the research provides valuable insights for Alvina Hotel to refine its marketing strategies and enhance its competitive standing within the hospitality sector